Creating Connection by Design: Supporting Adult Learners by Building Inclusive Online Academic Communities - Kari Sheward; Carol Rogers-Shaw; Tulare W. Park (Adult Education Research Conference, 2022)
Students are struggling to build online connections in classrooms. This instructional model provides strategies for working with learners with social skill, mental health, and communication challenges to improve community.
Keywords: community; distance education; languishing; academic barriers; personal challenges